Metabolomic traits of Amomum villosum Lour. fruits from different areas in Asia - Zhihang Duan (Journal of Analytical Science and Technology, 2025)
Abstract Amomum villosum Lour. is an essential plant for both consumption and healing purposes. Among all the regions in China where A. villosum is grown, Yangchun City is widely regarded as the most ideal habitat for this plant. However, there were rare studies that explored the differential metabolites between Yangchun and other regions of A. villosum fruits. The current study analyzed the metabolic profiles of A. villosum fruit samples cultivated in four representative producing areas. As a result, 260 differentially accumulated metabolites were identified in the GDYC-F versus LW-F. A total of 224 differentially accumulated metabolites were identified in the GDYC-F versus MD-F. A total of 285 differentially accumulated metabolites were identified in the YNML-F versus LW-F. A total of 262 differentially accumulated metabolites were identified in the YNML-F versus MD-F. Moreover, we identified the biomarkers to distinguish samples from different regions, including 9,12,13-TriHOME, 2-Ketobutyric acid, alpha-linolenic acid, nobiletin, sodium deoxycholate, gluconolactone and adipic acid, mifepristone, Qing Hau Sau and p-Coumaroylquinic acid, coumarin, ciliatine, methyl benzoate, 1,3-Benzenediol, (2′E,4′Z,8E)-Colneleic acid and beta-D-Fructose 6-phosphate, phenylethylamine, 4-Nitrophenol and geranyl acetate. KEGG enrichment analysis revealed that ‘Linoleic acid metabolism’ and ‘Phenylpropanoid biosynthesis’ were significant metabolic pathways among the different comparisons. The research uncovered metabolic variances in A. villosum fruits between authentic (Yangchun) and non-authentic regions across various nations, providing a scientific foundation for evaluating habitat appropriateness and introducing superior A. villosum. Subsequent research ought to confirm this study’s findings by employing more sampling sites and gathering A. villosum fruits across successive years.